The development of low birth weight term infants and the effects of the environment in Northeast Brazil - Grantham-McGregor, Sally M.; Lira, Pedro I. C.; Ashworth, Ann; Morris, Saul Sutkover; Assuncao, Alicia M. S. (Elsevier, 1998)
Objectives: (1) To compare the mental and psychomotor development of low birth weight term (LBW-T) infants with that of appropriate birth weight (ABW) infants at 6 and 12 months of age. (2) To examine the relationship between developmental levels and social background... Conclusions: LBW-T infants had poorer development than ABW infants and differed in their behavior. There was an interaction between birth weight and the environment. LBW-T infants, but not ABW infants, were affected by the quality of stimulation in the home and maternal illiteracy.